Knowledge, attitude and acceptance among Undergraduate Students in Faculty of Health Science (FSK) and Faculty of Islamic Studies (FPI), Universiti Kebangsaan Malaysia (UKM) towards covid-19 Vaccines - Nurul Farhana Jufri,; Nor Atikah Mohd Musta’aim,; Nurul Shafika Ahmad Sofi,; Nurul ‘Izzah Solah,; Nur Ruzana Razani,; Theedaraj Bun Chuan,; Aswini Kumareswaran,; Ahmad Muhaimin Che Hasan, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The best hope for a long-term solution to the COVID-19 pandemic is the development of a vaccine. A vaccination must, however, be accepted and utilised by the vast majority of people in order to achieve herd immunity. Therefore, this study aims to investigate the knowledge, attitude and acceptance of COVID-19 vaccine among the students in the Faculty of Health Science (FSK) and Faculty of Islamic Studies (FPI) of Universiti Kebangsaan Malaysia (UKM). This is a cross-sectional study, and the questionnaire was conducted through an online platform. The questionnaire was then distributed to the third-year students of FSK and FPI of UKM. Respondents’ demographic information was gathered and the knowledge, attitudes and acceptance score of the participants towards COVID-19 vaccine were calculated and classified according to their faculty. The relationship between knowledge regarding COVID-19 and the acceptance of COVID-19 vaccine was identified by using the Chi-Square test. The association between attitude and acceptance towards COVID-19 vaccine was also determined by using the same test. 143 students participated in this study where 80 (55.9%) of them are from FSK and 63 (44.1%) are from FPI. Majority of the respondents are female and aged 22-25 years old with Malay being the highest race of respondents. Both faculties have the same level of knowledge regarding COVID-19 which are on the moderate level with FSK (81.25%) and FPI (76.19%) respectively. Next, 55% of FSK students have a high level of attitude while 52.34% of FPI students have a medium level of attitude towards COVID-19 vaccine. In addition, the majority of both students from FSK (97.5%) and FPI (85.72%) will definitely accept the COVID-19 vaccine. Furthermore, there is a relationship between knowledge regarding COVID-19 and acceptance towards COVID-19 vaccines among FSK and FPI students (p = 0.009, p<0.05) but there is no relationship between attitude and acceptance towards COVID-19 vaccine (p = 0.627, p>0.05). Respondents from both faculties reported high acceptance of COVID-19 vaccines. Further studies can be done regarding the specific factors affecting their knowledge, attitude, and acceptance towards COVID-19 vaccines.